Automatic Detection and Correction of Detuned Singing System for Use With Query-By-Humming Applications - LECH, Michał (Archives of Acoustics, 2008)
The aim of the paper is to present an idea of using the automatic detection and correction of detuned singing as a subsystem in query-by-humming (QBH) applications. The common approach to searching for a requested song basing on the melody retrieved from hummed pattern usually employs the so-called Parsons code or melody contour. In such a case information about sound pitch is discarded. It was thought out that an additional module added to the QBH system indicating notes which were sung out of tune and correcting them might be useful. For this purpose two fundamental frequency detection algorithms, i.e. the fast autocorrelation and HPS (Harmonic Product Spectrum), and two pitch shifting algorithms, i.e. the modified phase vocoder and PSOLA (Pitch-Synchronous Overlap-Add) are chosen and examined. Four possible combinations of the algorithms are reviewed in the context of correctness of the fundamental frequency detection and pitch shifting. Basing on the results, the sub-system for automatic detection and correction of detuned singing for use with QBH applications is implemented. In addition, listening tests and objective measurements of the obtained pitch correction are performed. Conclusions are drawn and proposals of further improvements are provided.